2010
DOI: 10.1590/s0102-86502010000100022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acetone cyanohydrin effect in "in vitro" inativation of the Ehrlich ascites tumor cells

Abstract: , more than 90% of cell death was observed only after 24 hours of incubation which is the evidence that the tumor cell has the ability to poison cumulatively and irreversibly itself with the acetone cyanohydrin when compared with the results presented by human lymphocytes that the same doses and at the same time of incubation reached a maximum of 30% of cell death, suggesting an activity of rhodanese differentiated between the two cells. Key words: Carcinoma, Ehrlich Tumor. Acetone. Neoplasms. In vitro. ), dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…by the seventh day after inoculation and showed varying shapes and The action of cyanogenic chemotherapy using AC as cyanide source in the experiment developed suggests the ability of tumor cells to irreversibly poison the action of cyanide, thereby providing a dose-and time-dependent effect 12, , as occurred in previous studies 8,9 . Cyanide toxicity occurs in two ways: ATP depletion caused by blockage of oxidative phosphorylation and production of reactive oxygen species 12 .…”
Section: All Inoculated Animals Developed Solid Ehrlich Tumor (Set)mentioning
confidence: 54%
See 1 more Smart Citation
“…by the seventh day after inoculation and showed varying shapes and The action of cyanogenic chemotherapy using AC as cyanide source in the experiment developed suggests the ability of tumor cells to irreversibly poison the action of cyanide, thereby providing a dose-and time-dependent effect 12, , as occurred in previous studies 8,9 . Cyanide toxicity occurs in two ways: ATP depletion caused by blockage of oxidative phosphorylation and production of reactive oxygen species 12 .…”
Section: All Inoculated Animals Developed Solid Ehrlich Tumor (Set)mentioning
confidence: 54%
“…This quite possibly occurs by a defect in the detoxification process of cyanide in tumor cells involving cell stocks of sulfur, in which they are easily intoxicated even with low doses of cyanide 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The residual cyanide aspect has been addressed in recent research and these investigations have shown that this component has relevant biological activity when in low concentrations. [40] show that cyanide is a compound that is toxic to all forms of aerobic life, inasmuch as it causes the inhibition of the mitochondrial respiratory chain, even though normal human cells have as a defense to its toxicity the rhodanese enzymes, which are found in low amounts in cancer cells. The authors also show that the antineoplastic action will have an e ciency of 80% at a tumor suspension concentration of 20 µg CN mL − 1 during the incubation of 2 hours in in vitro tests.…”
Section: Bioactive Secondary Compounds and Antioxidant Activitymentioning
confidence: 99%
“…Values of residual cyanide present in the our were extremely low (Table 3), with a variation of 0.50 to 4.20 mg kg − 1 in the Dry Class our, 0.99 to 4.70 mg kg − 1 in Fermented our samples and 4.12 to 15.60 mg kg − 1 in Mixed samples. Such ndings as to the presence of this compound can act positively and give greater visibility to the product, without the risk of food poisoning [28,40].…”
Section: Bioactive Secondary Compounds and Antioxidant Activitymentioning
confidence: 99%
“…As one of the forms of tumor cell regression, cyaniding acetone (CA) has been used. It is only possible to perform this approach because of its molar equivalent of cyanide that is anchored in neoplastic cells and these cannot eliminate cyanide due to the reduction of sulphane compound (RAMALHO et al, 2013;CEREDA, 2010). According to Essers (1993 apud RAMALHO; AYDOS; CEREDA, 2010), cyanide is commonly found in the environment and both men and animals can be exposed through different forms found such as in water, plastics, acrylics, cigarette smoke and cyanogenic plants.…”
Section: Cyanogenic Substancesmentioning
confidence: 99%